Exploring attitudinal factors influencing modal shift: a latent class analysis of Danish commuters - Rasmussen, L. R.; Agerholm, N.; Lahrmann, H.; Olesen, A. V. (Frontiers in Future Transportation, 2023)
Governments advocate for a modal shift from motorized transport modes to active modes. Various political approaches can be adopted to affect travel behavior and patterns. However, interventions spread across the entire population offer limited opportunities to achieve behavioral change. Furthermore, attitude has been shown to cut across demographic characteristics and strongly influence the conducted travel behavior. Therefore, a latent class analysis including significant sociodemographic variables and value-based attitudes concerning factors influencing transport, settlement, and additional priorities was performed. The study objectively identified five classes of Danish commuters with the same preconditions in terms of commuting distance but with clear differences in attitude and transport modes. Each latent class represents a unique combination of characteristics, which indicates the need to design target group-specific interventions to optimize the chances of influencing travel behavior. In particular, a group of malcontented motorists demonstrating a high intention to change exhibit negative feelings toward car travel and thus appear to act in contravention of their attitudes. In contrast, a class of immovable motorists was found, a class of beneficial commuters and finally two cycling dominated classes of passionate cyclists and environmentalist cyclists. Finally, this study has emphasized that similar attitudes can lead to dissimilar behaviors and that the same behavior can be exhibited for various reasons. We deduced how transport mode choice is influenced by various factors, with habit as one of the strongest, as those with strong habits seem disinclined to information about alternatives and call for “harder” policy interventions. The findings emphasize the importance of targeted interventions tailored to specific commuter groups to encourage modal shifts towards sustainable transportation.